Purification and Characterization of Two Forms of Glutamine Synthetase from the Pedicel Region of Maize (Zea mays L.) Kernels - Muhitch, Michael J. (1989)
Maize (Zea mays L.) kernel pedicels, including vascular tissues, pedicel parenchyma, placento-chalazal tissue, and the surrounding pericarp, contained two forms of glutamine synthetase (EC 6.3.1.2), separable by anion exchange chromatography under mildly acidic conditions. The earlier-eluting activity (GS(p1)), but not the later-eluting activity (GS(p2)), was chromatographically distinct from the maize leaf and root glutamine synthetases. The level of GS(p1) activity changed in a developmentally dependent manner while GS(p2) activity was constitutive. GS(p1) and GS(p2) exhibited distinct ratios of transferase to hydroxylamine-dependent synthetase activities (5 and 23, respectively), which did not change with kernel age. Purified pedicel glutamine synthetases had native relative molecular masses of 340,000, while the subunit relative molecular masses differed slightly at 38,900 and 40,500 for GS(p1) and GS(p2), respectively. Both GS forms required free Mg(2+) with apparent K(m)s = 2.0 and 0.19 millimolar for GS(p1) and GS(p2), respectively. GS(p1) had an apparent K(m) for glutamate of 35 millimolar and exhibited substrate inhibition at glutamate concentrations greater than 90 millimolar. In contrast, GS(p2) exhibited simple Michaelis-Menten kinetics for glutamate with a K(m) value of 3.4 millimolar. Both isozymes exhibited positive cooperativity for ammonia, with S(0.5) values of 100 and 45 micromolar, respectively. GS(p1) appears to be a unique, kernel-specific form of plant glutamine synthetase. Possible functions for the pedicel GS isozymes in kernel nitrogen metabolism are discussed.